Respiratory snorkel and valve system for breath-by-breath gas analysis in swimming - Keskinen, K. L.; Rodriguez, F. A.; Keskinen, O. P. (Scandinavian Journal of Medicine & Science in Sports, 2003)
The present study aimed to compare a standard facemask (CM) and a newly modified swimming snorkel and valve system (SV) for breath-by-breath (BB) gas analysis (K4 b2, Cosmed, Rome, Italy), and to validate the system under controlled laboratory conditions before being used in swimming. Nine healthy males performed two bouts of a stepwise exercise on an electrically braked stationary bicycle on separate days. Ventilatory and gas exchange parameters were analyzed using the same BB portable system, with subjects breathing alternatively through the two different valves. Agreement between both methods was evaluated by Passing-Bablok regression analysis. The gas exchange values measured using the SV were highly correlated with those obtained using the CM (R2 values >0.9). However, differences existed between the two series of measurements so that most ventilatory and gas exchange parameters were lower (3-7%) with the SV. The error when using the SV device was mainly systematic along the whole range of measurement. Accordingly, linear regression equations were developed to further improve the accuracy of the measures when using the SV. Therefore, the modified respiratory SV system can be considered as a valid device for collecting expired gas for BB analysis, comparable to the standard facemask, with the advantage of being suitable for measurements during swimming.